Transmisi Budaya dalam Praktik Bue’ Anak pada Masyarakat Sebulu Kabupaten Kutai Kartanegara - Saferi Yohana; Irma Surayya Hanum; Eka Aprilia Putri; Aufa Maryam; Muadz Madhani (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2026)
This study aims to analyze the mechanisms of cultural transmission in the practice of  bue' anak, identify the shifts that occur, and understand the meanings that perpetuate cultural meanings in parenting practices. The research method used is a qualitative approach with an interpretive ethnographic framework. Data were collected through observation and in-depth interviews. The data were then analyzed using Clifford Geertz's cultural interpretation approach and supplemented with the habitus and practices of cultural transmission. The results indicate that bue' anak is a cultural transmission practice that occurs orally and naturally through custom, imitation, and intergenerational interaction. This practice serves not only as a means of lulling children to sleep but also as a means of establishing emotional connections, representing values, and strengthening cultural identity through language, symbols, and bodily experiences. However, in the modern context, this practice has undergone a shift marked by the increasing use of digital technology as a substitute for live singing. This change has resulted in a reduction in emotional interaction and the potential loss of cultural meanings inherent in the practice of bue' anak.